Cinematografias do fantástico: visões de Alice e do País das Maravilhas no cinema - Fernanda de Cassia Alves Salgado (2012)
From the same starting point the two novels written by Lewis Carroll, Alice's Adventures in Wonderland (1865) and Through the Looking-Glass and What Alice Found There (1871) , this dissertation seeks to show the different modalities that the carrollian fantastic assumes when it is recreated and adapted by five different filmmakers. The movies investigated are: Alice in Wonderland (1951), by Clyde Geronimi, Wilfred Jackson and Hamilton Luske, from Walt Disney Productions; BlackMoon (1975), by Louis Malle; Alice or the last escapade (1977) by Claude Chabrol; Alice (1988), by Jan vankmajer; and Alice in Wonderland (2010), by Tim Burton. In order to do such investigation, this paper characterizes the fantastic as a place of ambiguity, antinomical existence between real and unreal and with language displacements. We also investigate how each filmmakers narrative and structural proceedings recreate Carrolls fantastic universes and characters in theircinematographic works.